História em quadrinhos como estratégia comunicacional para educar sobre preconceito linguístico - Kawashima, Fernanda Lazari [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This term paper, developed in an experimental project format (product), is composed by a communicational material about linguistic prejudice. Based on the belief of the existence of only one portuguese language that deserves to be called like that, this prejudice form, according to Marcos Bagno (2007), causes the different linguistic variations of the standard language to be understood as “wrong” or “inadequate”. Consequently, the people who use the language that is considered “incorrect”, sometimes, may suffer discrimination because of it. Therefore, strategies are needed to face and denaturalize the use of violence in language. Thereupon, we believe that this material can contribute with all of the other educational efforts that aim to deconstruct this prejudice. Indeed, this deconstruction is fundamental because, according to Noleto (2010), values like respect to the cultural diversity, freedom and tolerance are essential to a culture of peace. Therefore, this material aims to present a communicational and didactic proposal to be worked with students between seven and ten years old in schools of São Paulo state inland. It is composed by a comic, a guide to orient teachers about how to work the theme in the classroom and an insert with activities. The chosen format to the material accords to the principles defended by Santos (2013), which says that the comics can spark the interest in learning. We believe that, with the playful activities that approach the linguistic prejudice, the children become familiar to the debate and start a self-knowledge process about their own culture and the cultural diversity that surrounds them.

O presente trabalho de conclusão de curso, realizado em formato de projeto experimental (produto), é composto por um material comunicacional sobre preconceito linguístico. Baseado na crença da existência de uma única língua portuguesa que deva ser assim chamada, tal forma de preconceito, segundo Marcos Bagno (2007), faz com que as distintas variações linguísticas da norma culta padrão sejam compreendidas como “incorretas” ou “inadequadas”. Consequentemente, as pessoas que fazem uso de tal linguagem considerada “incorreta”, por vezes, podem vir a sofrer discriminações. Portanto, são necessárias estratégias para enfrentar e desnaturalizar o uso da violência na linguagem. Por essa razão, acreditamos que este material pode contribuir com os demais esforços educacionais voltados para descontruir tal preconceito. De fato, essa desconstrução é fundamental porque, segundo Noleto (2010), valores como respeito à diversidade cultural, liberdade e tolerância são essenciais para uma cultura de paz. Portanto, este material visa apresentar uma proposta comunicacional e didática a ser trabalhada com estudantes entre 7 a 10 anos em escolas do interior do estado de São Paulo. Está composto por uma história em quadrinhos, um guia para orientar professores sobre como trabalhar a temática em sala de aula, e um encarte de atividades. O formato escolhido para o material atende aos princípios defendidos por Santos (2013), de que a história em quadrinhos pode despertar o interesse pela aprendizagem. Acreditamos que mediante atividades lúdicas que abordam o preconceito linguístico, a criança se familiariza com o debate e começa um processo de autoconhecimento de sua própria cultura e da diversidade cultural que a cerca.
Comics as a communication strategy to educate about linguistic prejudice
Keywords: Linguistic prejudice; Communication; Education; Comics; Preconceito linguístico; Comunicação; Educação; História em quadrinhos